Transboundary pollution, R&D spillovers, absorptive capacity and international trade - Zeineb Dinar (Kiel Institute for the World Economy (IfW), 2013)
In this paper, we consider a non-cooperative and symmetric three-stage game model composed by two regulator-firm hierarchies. By means of adequate emission taxes, original and absorptive research and development (R&D) subsidies we prove that regulators can reach the non-cooperative social optimum. In the presence of free R&D spillovers between countries, as well as the investment in absorptive research, the competition of firms on a common market helps non-cooperating countries to better internalize transboundary pollution. We find that in autarky and common market cases the investment in absorptive R&D leads to multiple non-cooperative equilibria, which may necessitate competing regulators to coordinate an equilibrium. Interestingly, opening markets to international trade increases the per-unit emission-tax and the per-unit original research subsidy. It causes a higher investment in original research and production, and a lower emission ratio.
Keywords: C72; H21; O32; D62; 330; Transboundary pollution; R&D spillovers; absorptive capacity; international trade